The Contribution of Sharia Investment Instruments to Economic Development in Indonesia: Opportunities and Challenges of Precious Metals - Rukiah Rukiah (PT. Anagata Sembagi Education, 2025)
Global economic developments and increasing public awareness of halal finance are driving the growth of Islamic investment instruments in Indonesia. This study aims to analyze the contribution, opportunities, and challenges of Islamic investment instruments, including Islamic stocks, sukuk, Islamic mutual funds, and precious metal commodities, in the development of the Muslim economy. The research method used is a qualitative descriptive approach supported by quantitative data through documentation studies, content analysis, descriptive quantitative analysis, and SWOT analysis. The results indicate that Islamic investment instruments have a strategic role in strengthening the real sector, increasing financial inclusion and literacy among Muslims, and maintaining economic stability through the principles of justice, transparency, and sustainability in accordance with the maqasid al-shariah. Specifically, precious metals, especially gold, contribute as a hedging instrument, provide access to non riba financing, and strengthen the microeconomic resilience of the Muslim community. However, the development of Islamic investment instruments still faces challenges such as low Islamic financial literacy, limited product innovation, global market fluctuations, and suboptimal synergy among stakeholders. Therefore, strengthened regulations, public education, Islamic governance, and inclusive product innovation are needed so that Islamic investment instruments can function optimally as a driving force for equitable and sustainable Islamic economic development in Indonesia.